Three-Dimensional Modeling of Thyroid Hormone Metabolites Binding to the Cancer-Relevant αvβ3 Integrin: In-Silico Based Study - Tobi, Dror; Krashin, Eilon; Davis, Paul J.; Cody, Vivian; Ellis, Martin; Ashur-Fabian, Osnat (Frontiers in Endocrinology, 2022)
Background: Thyroid hormones (TH), T4 and T3, mediate pro-mitogenic effects in cancer through binding the membrane receptor αvβ3 integrin. The deaminated analogue tetrac blocks TH binding to this receptor and prevents their action. While computational data on TH binding to the https://www.frontiersin.org/my-frontiers/overview integrin was published, a comprehensive analysis of additional TH derivatives is lacking. Methods: In-silico docking of 26 TH metabolites, including the biologically active thyroid hormones (T3 and T4) and an array of sulfated, deiodinated, deaminated or decarboxylated derivatives, to the αvβ3 receptor binding pocket was performed using DOCK6, based on the three-dimensional representation of the crystallographic structure of the integrin. As the TH binding site upon the integrin is at close proximity to the well-defined RGD binding site, linear and cyclic RGD were included as a reference. Binding energy was calculated for each receptor-ligand complex using Grid score and Amber score with distance movable region protocol. Results: All TH molecules demonstrated negative binding energy, suggesting affinity to the αvβ3 integrin. Notably, based on both Grid and Amber scores sulfated forms of 3,3' T2 (3,3' T2S) and T4 (T4S) demonstrated the highest binding affinity to the integrin, compared to both cyclic RGD and an array of examined TH derivatives. The major thyroid hormones, T3 and T4, showed low Amber score binding energy with high affinity to the integrin, which was higher than that of linear RGD. For all hormone derivatives, decarboxylation led to decreased affinity. This corresponds with the observation that the carboxylic group mediates binding to the integrin pocket via divalent cations at the metal-ion-dependent adhesion (MIDAS) motif site. A similar reduced affinity was documented for deaminated forms of T3 (triac) and T4 (tetrac). Lastly the reverse forms of T3, T3S, and T3AM show lower affinity relative to their native form, indicating that iodination at position 5 is associated with increased binding energy compared to position 5'. Summary: Three-dimensional docking simulation of various TH derivatives uncovered a structural basis for a differential computational binding energy to the αvβ3 integrin. These findings may suggest that naturally occurring endogenous TH metabolites may impact integrin-mediate intracellular pathways in physiology and cancer